1998
DOI: 10.1073/pnas.95.19.11187
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of hematopoietic cells by the Ski oncoprotein involves repression of retinoic acid receptor signaling

Abstract: The Ski oncogene has dramatic effects on the differentiation of several different cell types. It induces the differentiation of quail embryo cells into myoblasts and arrests the differentiation of chicken hematopoietic cells. The mechanism that Ski uses to carry out these disparate biological activities is unknown. However, we were struck by the similarity of these effects to those of certain members of the nuclear hormone receptor family. Both Ski and the thyroid hormone receptor-derived oncogene v-ErbA can a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 42 publications
0
70
1
Order By: Relevance
“…[9][10][11] Because Dahl et al 12 showed that Ski could be involved in the repression of RAR signaling and we found a lower SKI expression in the more differentiated AML subgroups (e.g. t(15;17)), we decided to further investigate Ski and its interference with the RARa signaling pathway in AML.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Because Dahl et al 12 showed that Ski could be involved in the repression of RAR signaling and we found a lower SKI expression in the more differentiated AML subgroups (e.g. t(15;17)), we decided to further investigate Ski and its interference with the RARa signaling pathway in AML.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we and others reported that Ski expression is highly upregulated in bone marrow samples from patients with monosomy 7 or deletion 7q acute myeloid leukemia (AML) and CD34 þ cells from patients with chronic myelogenous leukemia (CML) (Kronenwett et al, 2005;Ritter et al, 2006). The effect of Ski on PU.1 might render Ski a more potent inhibitor of cell differentiation in cooperation with its known repression activity in retinoic acid signaling in myeloid cells (Dahl et al, 1998;Ritter et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…His-tagged PU.1 and GST or GST-Ski were co-expressed in DH5a host strain and purified as described (Dahl et al, 1998). For each copurification, bacterial lysate containing 1 mg of GST fusion protein was applied to Glutathione Sepharose 4B (GE Healthcare), washed extensively in phosphate-buffered saline (PBS) containing 0.5% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations